A combined randomised and observational study of surgery for fractures in the distal radius in the elderly (CROSSFIRE)—a study protocol. Issue 6 (23rd June 2017) - Harris, Ian, A; Naylor, Justine, M; Lawson, Andrew; Buchbinder, Rachelle; Ivers, Rebecca; Balogh, Zsolt; Smith, Paul; Mittal, Rajat; Xuan, Wei; Howard, Kirsten; Vafa, Arezoo; Yates, Piers; et al.
Abstract : Fractures of the distal radius are common and occur in all age groups. The incidence is high in older populations due to osteoporosis and increased falls risk. Considerable practice variation exists in the management of distal radius fractures in older patients ranging from closed reduction with cast immobilisation to open reduction with plate fixation. Plating is currently the most common surgical treatment. While there is evidence showing no significant advantage for some forms of surgical fixation over conservative treatment, and no difference between different surgical techniques, there is a lack of evidence comparing two of the most common treatments used: closed reduction and casting versus plating. Surgical management involves significant costs and risks compared with conservative management. High-level evidence is required to address practice variation, justify costs and to provide the best clinical outcomes for patients. Methods and analysis: This pragmatic, multicentre randomised comparative effectiveness trial aims to determine whether plating leads to better pain and function and is more cost-effective than closed reduction and casting of displaced distal radius fractures in adults aged 60 years and older. The trial will compare the two techniques but will also follow consenting patients who are unwilling to be randomised in a separate, observational cohort. Inclusion of non-randomised patients addresses selection bias, provides practice and outcome insights about standard care, and improves the generalisability of the results from the randomised trial. Ethics and dissemination: CROSSFIRE(Combined Randomised and Observational Study of Surgery for Fractures In the distal Radius in the Elderly) was reviewed and approved by The Hunter New England HREC (HNEHREC Reference No: 16/02/17/3.04). The results of the trial will be published in a peer-reviewed journal and will be disseminated via various forms of media. Results will be incorporated in clinical recommendations and practice guidelines produced by professional bodies. Registration: CROSSFIRE has been registered with the Australian and New Zealand Clinical Trials Registry (ANZCTR: ACTRN12616000969460).